2020
DOI: 10.1097/mot.0000000000000822
|View full text |Cite
|
Sign up to set email alerts
|

Measuring human leukocyte antigen alloantibodies: beyond a binary decision

Abstract: Purpose of review Accurate measurement of human leukocyte antigen antibodies is critical for making clinical decisions treating patients awaiting transplantation or monitoring them post transplantation. Single antigen bead assay results are given as Mean Fluorescence Intensity, falling short of providing the required quantitative measure. Recent findings Titration studies were shown to circumvent the limitation of target-saturation that affect interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…There is a maximum number of antigens on these beads. Bead saturation and interference can occur leading to inaccurate results particularly among patients with a high quantity of HLA antibody ( 38 , 39 ). Performing these solid phase assays with diluted serum to determine antibody titer can provide a better quantitative assessment Figure 1 .…”
Section: Considerations For Outcome Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a maximum number of antigens on these beads. Bead saturation and interference can occur leading to inaccurate results particularly among patients with a high quantity of HLA antibody ( 38 , 39 ). Performing these solid phase assays with diluted serum to determine antibody titer can provide a better quantitative assessment Figure 1 .…”
Section: Considerations For Outcome Assessmentmentioning
confidence: 99%
“…As shown in these violin plots, the quantity of donor specific antibody can be vastly different (different titer) despite the same MFI. This emphasizes the point that MFI is not a reliable endpoint for DSA quantification in treatment trials(38). Reprinted with permission from Maguire CH, Schinstock CA, Tambur AR.…”
mentioning
confidence: 99%
“…For all titration experiments performed by Luminex, we utilized HLA-coated single antigen beads (SAB) from ThermoFisher/OneLamda (West Hills/CA/USA). 40 To circumvent the 'shared-epitope-phenomenon', 41,42 we used individual bead sets (SAB mono ), representing a single HLA type only. For each SAB titr -assay, we additionally used negative (uncoated) control beads (NCB).…”
Section: Single Hla Beadsmentioning
confidence: 99%
“…We have shown that despite having the same cPRA (99.9% at baseline) on undiluted serum sample, our cohort exhibited significant heterogeneity with regards to HLA antibody strength. Thus, the major advantage of combining cPRA calculation with serum dilution is the ability to incorporate two different metrics of sensitization (1) the breadth of sensitization and (2) the quantity of antibodies 21 . This key information can be used to identify patients presumed to be most likely to respond to desensitization at baseline (e.g., identify patients to include in desensitization trials) and the reduction in cPRA per dilution could be used as an endpoint to compare the efficacy of various therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the major advantage of combining cPRA calculation with serum dilution is the ability to incorporate two different metrics of sensitization (1) the breadth of sensitization and (2) the quantity of antibodies. 21 This key information can be used to identify patients presumed to be most likely to respond to desensitization at baseline (e.g., identify patients to include in desensitization trials) and the reduction in cPRA per dilution could be used as an endpoint to compare the efficacy of various therapies. An additional advantage of this measure is that it is sensitive enough to identify therapeutic efficacy that may not have been apparent with other endpoints.…”
Section: Introductionmentioning
confidence: 99%